Invasive wild boar (Sus scrofa) as a functional reservoir for the dynamics of Trichinella in the Patagonia region - Chang Reissig, Elizabeth (2024)
Trichinellosis is a zoonotic disease that has been studied mainly in domestic pigs (Sus scrofa domesticus). The cycle involves infection in domestic and wild fauna, which fulfill complex ecological roles, where Trichinella spiralis is reported in wild boar (Sus scrofa). The objective of this study was to determine the prevalence of trichinellosis in wild boar and evaluate the distance of positive animals to the nearest urbanization areas in Argentina Patagonia. Necropsies were carried out on wild boar hunted in the Nahuel Huapi and Lanín National Parks and surrounding areas. Skeletal muscle samples were collected from 1,694 wild boar and artificial digestion was performed on all samples. Trichinella spp. were found in 96 of 1,694 (5.8%) wild boar (0.2 to 424 Larvae/g). Parasitism in wild boar depends on the distribution of the population in natural and urban areas. Infected wild boar were found near peri-urban areas, demonstrating the importance of routine epidemiological surveillance and sanitary measures in and around cities. More research is needed to identify the types of Trichinella species that infect wild animals. We recommend the application of active and passive epidemiological surveillance in South America on exotic and native fauna that are hunted and consumed by humans.